Pengaruh Penerapan Remote Audit pada Kualitas Audit Internal Pasca Pandemi Covid-19 - Setiyawan, Dany (Politeknik Ganesha Medan, 2024)
Despite the challenges encountered in the field, audit quality within the scope of internal audit remains a top priority. The study outlines the ways in how remote audits impact audit quality and the approaches implemented by internal auditors to enhance audit quality. Examining the effect of remote auditing on audit quality is appropriate given the COVID-19 pandemic. This combination of auditor competence and time budget pressure to moderate the effect of remote audits on internal audit quality are also addressed in this study. Survey data is used in this study to measure how far APIP in East Java Province began using remote auditing after the epidemic. SmartPLS is used in the analytical method combined with the Structural Equation Modeling (SEM) model such as reliability and convergent validity test, discriminant validity test and PLS path algorithm and bootstrapping test. The research questionnaire's are measured using a Likert scale (1-7). Remote audits have a positive effect on improving internal audit quality, according to the result of a survey conducted towards 76 out of 100 internal auditors. But auditor competence and time budget pressure does not significantly moderate such a relationship. The research's conclusions have significance for practitioners looking to improve audit quality in remote audits and may benefit users of financial reports to comprehend the level of audit quality in remote audits